Study the Influence of Antimony Dopant and Annealing on Structural, Optical and Hall Parameters of AgInSe2 Thin Film - Sobhi, Suha Nabeel; Hussein, Bushra H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
Sb-dopedAgInSe2 (AIS: 3%Sb)thin films were synthesized by thermal evaporation with a vacuum of 7*10-6torr on glass with (400+20) nm thickness. X-ray diffraction was used to show that Sb atoms were successfully incorporated into the AgInSe2 lattice. Then the thin films are annealed in air at 573 K. XRD shows that thin films AIS pure, AIS: 3%Sb and annealing at 573 K are polycrystalline with tetragonal structure with preferential orientation (112).raise the crystallinity degree. The Absorption spectra revealed that the average Absorption was more than 60% at the wavelength range of 400–700 nm. UV/Visible measure shows the lowering in energy gap to 1.4 eV forAIS: 3%Sb at 573 Kt his energy gap making these samples suitable for photovoltaic application, The electric property was better when AgInSe2: 3%Sb at 573 K , thin films were of donor type and the concentration of electrons in them increased with increasing Sb doped and annealing temperature.